PENETAPAN KADAR VITAMIN C PADA DAUN JELATANG (Urtica dioica L.) DENGAN MENGGUNAKAN SPEKTROFOTOMETRI ULTRAVIOLET - Zuhairiah Nasution; Siti Nurbaya; Supartiningsih Supartiningsih; Tiurma Sitompul (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Nettle leaf (Urtica dioica L) is the most widely known species in the genus Urtica and has many benefits for the community, one of which is to treat venereal diseases, kidney disorders, allergies, diabetes, anemia, and digestive tract diseases. Vitamins contained in nettle leaves that are useful for the body is vitamin C. Vitamin C has properties that are easily damaged by heat, and easily soluble in water. This study aims to determine the levels of vitamin C in young and old nettle leaves by an ultraviolet spectrophotometric method using Aquadest solvent and read a wavelength of 265 nm with a linear regression equation y= ax + b with a value of y= 0.0525 + 0.0618 with r = 0.9878 each treatment was replicated 6 times. Based on the results of the qualitative test experiment, it was stated that in nettle leaves there was vitamin C with iodine solution reagent, FeCl3, Fehling A&B, and obtained vitamin C levels in old nettle leaves 0.2526 mg/g and in young nettle leaves 0.2026 mg/g. So that the levels of vitamin C in old nettle leaves are higher than in young nettle leaves.